Dynamics of Farmers Group in Production of Barangan's Banana Business (Case Study in Lekke Farmer, Tonronge Village, Lappariaja District, Bone Regency). Issue 3 (July 2021) - Heliawaty,; Diansari, P; Lanuhu, N; Lumoindong, Y; Fudjaja, L; Bakri, R; Hamzah, Z
Abstract: South Sulawesi is one of the provinces with high banana production and one of the most popular types of banana is "Banana Barangan". Barangan banana is a leading commodity in Bone Regency with the production center located in Lappariaja District which is cultivated by the Lekke Farmer Group. This study aims to determine the dynamics of farmer groups in barangan banana farming. The research was conducted in Tonronge Village, Lappariaja District, Bone Regency in June-July 2016. Research respondents were all members of the Lekke Farmers Group. The study used a qualitative analysis using scoring to determine the level of dynamism of the farmer groups. The results of the study show that the dynamics of the Lekke Farmer Group is in the high category, from the six elements or indicators, the group atmosphere gets a high percentage with an average score of 11.4. It is expected to increase group dynamics in order to achieve common goals effectively and efficiently.